Genetic Manipulation of Carotenoid Biosynthesis in the Green Sulfur Bacterium Chlorobium tepidum - Frigaard, Niels-Ulrik (American Society for Microbiology, 2004)
The green sulfur bacterium Chlorobium tepidum is a strict anaerobe and an obligate photoautotroph. On the basis of sequence similarity with known enzymes or sequence motifs, nine open reading frames encoding putative enzymes of carotenoid biosynthesis were identified in the genome sequence of C. tepidum, and all nine genes were inactivated. Analysis of the carotenoid composition in the resulting mutants allowed the genes encoding the following six enzymes to be identified: phytoene synthase (crtB/CT1386), phytoene desaturase (crtP/CT0807), ζ-carotene desaturase (crtQ/CT1414), γ-carotene desaturase (crtU/CT0323), carotenoid 1′,2′-hydratase (crtC/CT0301), and carotenoid cis-trans isomerase (crtH/CT0649). Three mutants (CT0180, CT1357, and CT1416 mutants) did not exhibit a discernible phenotype. The carotenoid biosynthetic pathway in C. tepidum is similar to that in cyanobacteria and plants by converting phytoene into lycopene using two plant-like desaturases (CrtP and CrtQ) and a plant-like cis-trans isomerase (CrtH) and thus differs from the pathway known in all other bacteria. In contrast to the situation in cyanobacteria and plants, the construction of a crtB mutant completely lacking carotenoids demonstrates that carotenoids are not essential for photosynthetic growth of green sulfur bacteria. However, the bacteriochlorophyll a contents of mutants lacking colored carotenoids (crtB, crtP, and crtQ mutants) were decreased from that of the wild type, and these mutants exhibited a significant growth rate defect under all light intensities tested. Therefore, colored carotenoids may have both structural and photoprotection roles in green sulfur bacteria. The ability to manipulate the carotenoid composition so dramatically in C. tepidum offers excellent possibilities for studying the roles of carotenoids in the light-harvesting chlorosome antenna and iron-sulfur-type (photosystem I-like) reaction center. The phylogeny of carotenogenic enzymes in green sulfur bacteria and green filamentous bacteria is also discussed.